Paul Gauguin and the Quest for World Spirituality - Iswahyudi (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2021)
Paul Gauguin was born in Paris, France on June 7, 1848. The dynamics of his life journey greatly motivated his search for something deeper and more meaningful in his life and work. Gauguin's disillusionment with the bourgeois society in his environment and his desire to create his art works encouraged his decision to devote himself totally as an artist, especially outside his environment. He traveled from one region to another outside Europe. This experience will influence his development as a painter. The trips that Gauguin often undertook were influenced by his work as well as seeking broader and deeper experiences. As a European he sought a "primitive" lifestyle that was neither tangible nor considered "exotic". He is looking for geographic answers to his professional and personal searches while living in Tahiti. By examining his personal life, it is known that Gauguin's wandering led him to a deeper spiritual life, which is reflected in his works and writings. In order to understand the expression of spirituality in his work, we will examine several major works by Gauguin that clearly depict images of Buddhism and other Eastern religions.